Carnegie Supernova Project-II: Extending the Near-infrared Hubble Diagram for Type Ia Supernovae to z ∼ 0.1∗This paper includes data gathered with the 6.5 meter Magellan telescopes at Las Campanas Observatory, Chile. (27th November 2018) - Phillips, M. M.; Contreras, Carlos; Hsiao, E. Y.; Morrell, Nidia; Burns, Christopher R.; Stritzinger, Maximilian; Ashall, C.; Freedman, Wendy L.; Hoeflich, P.; Persson, S. E.; Piro, Anthony L.; Suntzeff, Nicholas B.; et al.
Abstract: The Carnegie Supernova Project-II (CSP-II) was an NSF-funded, four-year program to obtain optical and near-infrared observations of a "Cosmology" sample of ∼100 Type Ia supernovae located in the smooth Hubble flow (0.03 ≲  z  ≲ 0.10). Light curves were also obtained of a "Physics" sample composed of 90 nearby Type Ia supernovae at z  ≤ 0.04 selected for near-infrared spectroscopic timeseries observations. The primary emphasis of the CSP-II is to use the combination of optical and near-infrared photometry to achieve a distance precision of better than 5%. In this paper, details of the supernova sample, the observational strategy, and the characteristics of the photometric data are provided. In a companion paper, the near-infrared spectroscopy component of the project is presented.